Effect of concentration and brewing time on the antimicrobial activity of Camellia sinensis (green tea) against oral bacteria - Harpreet Singh Grover; Himanshu Deswal; Veenu Madaan Hans; L Sumitra Devi (Wolters Kluwer Medknow Publications, 2017)
Background and Aim: Green tea, a rich source of flavonoids, has tremendous oral health potential. This study evaluates the effect of brewing green tea at varying concentrations and duration on its antimicrobial activity against oral bacteria. Materials and Methods: Green tea was brewed in 15 concentration and time combinations. Paper disc diffusion test was carried out with these infusions on Tryptic Soy Agar plates inoculated with oral bacteria. Zone of inhibition after 72 h of incubation at 37°C was measured in millimeters. Results: Higher zone of inhibition was observed in concentration brewed for 15 min than 30 and 60 min. Zone of inhibition was directly proportional to the concentration of green tea brewed. Most effective concentration was 80 mg/ml with a mean of 2.83 mm which was significantly higher than mean zone of inhibition for 60 mg/ml (P < 0.05). Conclusion: Increasing the concentration and decreasing the brewing time of green tea results in a higher inhibitory effect on growth of oral bacteria.